(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research focuses on user issues and potential future developments related to net banking in Maharashtra, India. Although traditional banking affords well-settled convenience, digital surroundings offer a fast-growing alternative. The study examines the shift to internet banking while recognising the important role that IT plays in simplifying monetary offerings. Still, consumer concerns should be addressed if net banking is to become extensively used. Users’ pinnacle issue remains safety, as they worry about the safety of their monetary and personal data. In addition, users seeking help or resolving troubles may find it hard to conquer the absence of a face-to-face interaction that includes internet banking. The paper emphasises the numerous benefits of internet banking in spite of these worries. When compared to conventional strategies, users benefit from accessibility, convenience, and faster transactions. Furthermore, by casting off the desire for physical branches and the associated operating costs, internet banking has the potential to store charges for each bank and customer. In order to get a comprehensive comprehension of consumer viewpoints, the study utilises a survey instrument that is directed at human beings of different ages. Age has a statistically vast impact on some features of online banking, in keeping with the studies. For instance, more youthful users are much more likely to pay for advanced feature availability than older users, who price customised economic advice more noticeably. Focus groups and in-depth interviews are examples of qualitative processes that could provide insightful information on the underlying elements impacting user behaviour and choices. This thorough understanding is essential for creating in-depth solutions and encouraging Maharashtra to safely include cutting-edge online banking technologies.